EKSPRESI SUFISTIK PERJALANAN SALIK DAN CINTA ILLAHI DALAM PUISI INDONESIA - Sujarwoko Sujarwoko (Buana Bastra, 2014)
The differences of poetic style could be noticed from the expression. The expression of sufism in salik journey and God love in Indonesian poetry show various style_ ft could be noticed through the poetry of Abdul Hadi W.M., which chooses a dialogue expression between you and me, Sutardji Calzoum Bachri which comes from spell expression, and Kuntowijoyo which chooses praises style. These varieties of expression in Indonesian poetry show the journey of a variety of Indonesian culture history. Islam in Indonesia could be harmonized with culture and tradition.